2016
DOI: 10.1515/meceng-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of the Optimized Inverted Joined Wing Airplane Concept and Classical Configuration Airplanes

Abstract: The joined wing concept is an unconventional airplane configuration, known since the mid-twenties of the last century. It has several possible advantages, like reduction of the induced drag and weight due to the closed wing concept. The inverted joined wing variant is its rarely considered version, with the front wing being situated above the aft wing. The following paper presents a performance prediction of the recently optimized configuration of this airplane. Flight characteristics obtained numerically were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Tetrahedral meshes with prismatic layers to model the flow in boundary layer (BL) areas have been with ANSYS ICEM software. Such types of models have the capability of capturing not only turbulent flow in domain, but also laminar regions which potentially could have great influence on aerodynamic performance [41]. The mesh generated for the shapes I, II, III are presented in Fig.…”
Section: Cfd Analysis Of a Steady Sawtooth Motion At A Constant Angle...mentioning
confidence: 99%
“…Tetrahedral meshes with prismatic layers to model the flow in boundary layer (BL) areas have been with ANSYS ICEM software. Such types of models have the capability of capturing not only turbulent flow in domain, but also laminar regions which potentially could have great influence on aerodynamic performance [41]. The mesh generated for the shapes I, II, III are presented in Fig.…”
Section: Cfd Analysis Of a Steady Sawtooth Motion At A Constant Angle...mentioning
confidence: 99%
“…However, this theory does not apply to sweepangle wings. Adam Sieradzki et al [7] researched an inverted joined wing, with the front wing situated above the aft wing and connected at the wingtip. They found that the optimized lifting surface model of an inverted joined wing was better than the fixed-wing.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, software for multidisciplinary optimization was developed and applied so as to take structural analysis into consideration as well [42,43]. The overall conclusion was that the applied airplane configuration does allow for the construction of an airplane with better performance, although, as the results presented in [44] show, its advantage against conventional airplanes is nevertheless marginal. Moreover, the authors of this paper have concluded that the inverted joined wing shows superiority over the conventional one because of the adverse interference effects at high angles of attack.…”
Section: Introductionmentioning
confidence: 99%